2022
DOI: 10.1097/tin.0000000000000280
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Study of the Newest Vital Sign on Adolescents With Type 1 Diabetes and Healthy Adolescents in Turkish

Abstract: The current study aimed to establish validity and reliability of the Newest Vital Sign (NVS) in 255 Turkish adolescents aged 11 to 18 years with and without type 1 diabetes and evaluate their health literacy with age, gender, and health status. The t values of items in the NVS were found to be statistically significant and the calculated Cronbach's α coefficient value indicated that the reliability is at a medium level; 7.5%, 42%, and 56.5% of adolescents had respectively inadequate, limited, and adequate heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The identified studies used various types of health literacy related to the following health topics: general health31 32 34 35 42–67; nutrition68–82; non-communicable diseases (NCDs)36 63; HIV83 84; e-health39 85–91; media92; physical health93 94; oral health38 95; medical96; disability67 97 98; mental health37 40 41 99–108; suicide109 110; and depression 33 111. These studies used 36 scales to measure health literacy, and these scales can be grouped into three categories: newly developed scales66 77 82 86 93 98; newly adapted and translated scales33 40 41 43 54 55 64 69 83 96 100 111; and previously adapted and translated scales 34 35 38 39 44–46 49 51–53 56–59 62 65 67 68 71–73 76 78–80 85 87–89 91 95 97 103 104 107–110 112 113…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identified studies used various types of health literacy related to the following health topics: general health31 32 34 35 42–67; nutrition68–82; non-communicable diseases (NCDs)36 63; HIV83 84; e-health39 85–91; media92; physical health93 94; oral health38 95; medical96; disability67 97 98; mental health37 40 41 99–108; suicide109 110; and depression 33 111. These studies used 36 scales to measure health literacy, and these scales can be grouped into three categories: newly developed scales66 77 82 86 93 98; newly adapted and translated scales33 40 41 43 54 55 64 69 83 96 100 111; and previously adapted and translated scales 34 35 38 39 44–46 49 51–53 56–59 62 65 67 68 71–73 76 78–80 85 87–89 91 95 97 103 104 107–110 112 113…”
Section: Resultsmentioning
confidence: 99%
“…In this review, we identified several demographic and socioeconomic factors associated with health literacy: sex,37 39 42 45 47 49 55 62 63 74 76 90 94 95 101 104 higher income,39 47 51 64 90 97 98 parents’ working status,37 64 68 80 107 occupation,98 age,39 43 49 98 104 113 marital status,98 family type,89 90 ethnicity,44 degree of religiosity107 108 and social security 67. Moreover, health literacy was predicted by the educational level of adolescents, young adults and their parents37 45 47 53 64 68 72 80 89 90 92 95 101; grade at university or school37 39 43 57 67 73 87 95 97 113; years of education98; reading difficulties67; school achievement and academic disciplines57 64 65 70; and parental health literacy 48…”
Section: Resultsmentioning
confidence: 99%